Functionalization of the imidazo[1,2-a]pyridine ring in α-phosphonoacrylates and α-phosphonopropionates via microwave-assisted Mizoroki–Heck reaction - Kusy, Damian; Wojciechowska, Agata; Małolepsza, Joanna; Błażewska, Katarzyna M. (Beilstein Journal of Organic Chemistry, 2020)
A series of new phosphonocarboxylates containing an imidazo[1,2-a]pyridine ring has been synthesized via the microwave-assisted Mizoroki–Heck reaction. The efficient modification of the imidazo[1,2-a]pyridine ring has been achieved as late-stage functionalization, enabling and accelerating the generation of a library of compounds from a common precursor.
Keywords: α-phosphonoacrylates; α-phosphonopropionates; imidazo[1,2-a]pyridine; microwave-assisted reaction; Mizoroki–Heck reaction

(untitled) - Beletskaya, I. P.; Cheprakov, A. V. (Chem. Rev., 2000)

(untitled) - Yu, Y.; Su, Z.; Cao, H. (Chem. Rec., 2019)

(untitled) - Koubachi, J.; El Kazzouli, S.; Bousmina, M.; Guillaumet, G. (Eur. J. Org. Chem., 2014)

(untitled) - Frantz, R.; Granier, M.; Durand, J.-O.; Lanneau, G. F. (Tetrahedron Lett., 2002)

(untitled) - Mincheva, Z.; Courtois, M.; Andreu, F.; Rideau, M.; Viaud-Massuard, M.-C. (Phytochemistry, 2005)

(untitled) - Zheng, M.; Zhang, D. T.; Sun, M. X.; Li, Y. P.; Liu, T. L.; Xue, S. F.; Yang, W. J. (J. Mater. Chem. C, 2014)

(untitled) - Pietrusiewicz, M. K.; Kuźnikowski, M.; Koprowski, M. (Tetrahedron: Asymmetry, 1993)

(untitled) - Błażewska, K. M.; Ni, F.; Haiges, R.; Kashemirov, B. A.; Coxon, F. P.; Stewart, C. A.; Baron, R.; Rogers, M. J.; Seabra, M. C.; Ebetino, F. H.; McKenna, C. E. (Eur. J. Med. Chem., 2011)

(untitled) - Ebetino, F. H.; Hogan, A.-M. L.; Sun, S.; Tsoumpra, M. K.; Duan, X.; Triffitt, J. T.; Kwaasi, A. A.; Dunford, J. E.; Barnett, B. L.; Oppermann, U.; Lundy, M. W.; Boyde, A.; et al. (Bone, 2011)

(untitled) - Kaźmierczak, A.; Kusy, D.; Niinivehmas, S. P.; Gmach, J.; Joachimiak, Ł.; Pentikäinen, O. T.; Gendaszewska-Darmach, E.; Błażewska, K. M. (J. Med. Chem., 2017)

(untitled) - Joachimiak, Ł.; Marchwicka, A.; Gendaszewska-Darmach, E.; Błażewska, K. M. (ChemMedChem, 2018)

(untitled) - Kusy, D.; Maniukiewicz, W.; Błażewska, K. M. (Tetrahedron Lett., 2019)

(untitled) - Noël, T.; Buchwald, S. L. (Chem. Soc. Rev., 2011)

(untitled) - Monguchi, Y.; Ichikawa, T.; Yamada, T.; Sawama, Y.; Sajiki, H. (Chem. Rec., 2019)

(untitled) - Jagtap, S. (Catalysts, 2017)

(untitled) - Cini, E.; Petricci, E.; Taddei, M. (Catalysts, 2017)

(untitled) - Błażewska, K.; Gajda, T. (Tetrahedron, 2004)

(untitled) - Viciu, M. S.; Grasa, G. A.; Nolan, S. P. (Organometallics, 2001)

(untitled) - Wen, Q.; Jin, J.; Hu, B.; Lu, P.; Wang, Y. (RSC Adv., 2012)

(untitled) - Kou, X.; Zhao, M.; Qiao, X.; Zhu, Y.; Tong, X.; Shen, Z. (Chem. – Eur. J., 2013)

(untitled) - Kurandina, D.; Chuentragool, P.; Gevorgyan, V. (Synthesis, 2019)

(untitled) - Colbon, P.; Ruan, J.; Purdie, M.; Mulholland, K.; Xiao, J. (Org. Lett., 2011)

(untitled) - Melpolder, J. B.; Heck, R. F. (J. Org. Chem., 1976)

(untitled) - Whitcombe, N. J.; Hii, K. K.; Gibson, S. E. (Tetrahedron, 2001)

(untitled) - Veerakumar, P.; Thanasekaran, P.; Lu, K.-L.; Lin, K.-C.; Rajagopal, S. (ACS Sustainable Chem. Eng., 2017)